Peningkatan Keterserapan Lulusan SMKTI Muhammadiyah Cikampek dengan Bursa Kerja Khusus Berbasis Website - Tabrani, Muhamad; Sopandi, Robi; Abdussomad, Abdussomad (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
In the current era the development of information technology is very widespread, it is felt by the public. Utilization of information systems makes the main support system that runs and can produce information quickly, precisely and accurately. The system at the Special Occupational Vocational School of Muhammadiyah Cikampek in delivering job vacancies information is still ineffective, causing information not to be conveyed properly, and the registration process that uses forms and recorded in ledgers requires time in the process. Recording data manually can lead to errors in writing graduate identity data. Based on current developments, to increase the absorption of graduates in the world of work, the need for an effective and efficient media. This can utilize the website media which is expected to overcome various problems that occur in the Special Job Market, as well as facilitate graduates to obtain information on available vacancies and can register directly through the web, while also expected to help improve performance in managing the Job Market Specifically